Fatigue of glued-in rods in engineered hardwood products — part I: experimental results. Issue 5 (1st June 2019) - Myslicki, S.; Bletz-Mühldorfer, O.; Diehl, F.; Lavarec, C.; Vallée, T.; Scholz, R.; Walther, F.
ABSTRACT: Glued-in Rods (GiR) are among the high-performance joining technologies used in timber engineering. Engineering design procedures for GiR almost exclusively regulate softwood and softwood engineered wood products (EWP) under quasi-static loads. Since the use of hardwood is expected to significantly increase due to climate change, and potentially establish itself as predominant in Europe`s forests, GiR in combination with hardwood and corresponding EWP need to be investigated. Timber constructions subjected to cyclic loads are increasingly being used, as for example in timber bridges, high rise buildings, and wind turbine towers. No normative regulation is yet available for fatigue of GiR, which is for most part due to incomplete or completely missing experimental data. This paper is the first of a two part series; it presents fatigue investigations on GiR in combination with hardwood EWP with different types of rods, wood species and adhesives. Further, the embedment length and stress ratio were varried. In total, more than 70 cyclic tests were performed resulting in a high number of SN-curves showing the fatigue characteristics of GiR. The results show that two different damage mechanisms exist: in low cycle fatigue range (LCF), timber and adhesive fracture become dominant, while rod failure is the limiting factor in high cycle fatigue range (HCF). Based upon the documented experimental findings, existing standards for cyclic load on softwood connection technologies were discussed. The compagnion paper will present a design methodology based on a wood damage accumulation, giving a complete picture combined with existing metal fatigue models.